2014
DOI: 10.1007/s00231-014-1403-4
|View full text |Cite
|
Sign up to set email alerts
|

Transient volumetric heat transfer coefficient prediction of a three-phase direct contact condenser

Abstract: An experimental investigation for the time dependent volumetric heat transfer coefficient of the bubbles type, three-phase direct contact condenser has been carried out utilising a short column (70 cm in total height and 4 cm inner diameter). A 47 cm active height was chosen with five different mass flow rate ratios and three different initial dispersed phase temperatures. Vapour pentane and constant temperature tap water as dispersed and continuous phases were implemented. The results showed that the volumetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…And some research results showed that the efficient energy recovery can be enhanced by utilizing the direct contact condenser. [13] The direct contact condenser has many advantages compared with surface heat exchanger, such as simpler structure, lower investment cost, higher heat transfer rate, and less corrosion and fouling. Thus, direct contact condensers are also applied for industrial applications commonly.…”
Section: Irect Contact Condensation Occurs When Vapour Condensesmentioning
confidence: 99%
“…And some research results showed that the efficient energy recovery can be enhanced by utilizing the direct contact condenser. [13] The direct contact condenser has many advantages compared with surface heat exchanger, such as simpler structure, lower investment cost, higher heat transfer rate, and less corrosion and fouling. Thus, direct contact condensers are also applied for industrial applications commonly.…”
Section: Irect Contact Condensation Occurs When Vapour Condensesmentioning
confidence: 99%
“…Sideman and Hirsch, 1965;Isenberg and Sideman, 1970;Jacobs and Major, 1982;Higeta et al, 1983;Raina et al, 1984;Lerner et al, 1987;Wanchoo, 1993;Mori, 2002 andKalman, 2003) and bubble trains (Sideman and Moalem, 1974;Letan, 1990 andKalman, 2006). More recently, Mahood et al (2014aMahood et al ( , 2014bMahood et al ( , 2015aMahood et al ( , 2015b studied, experimentally and theoretically, the direct contact condensation of a swarm of two-phase bubbles in a three-phase condenser.…”
Section: Introductionmentioning
confidence: 96%
“…Although this study is not representative of a real three-phase direct contact condenser, it has improved the general understanding of the condensation of a swarm of two phase bubbles in an immiscible liquid. More recently, Mahood et al [17][18][19][20] have undertaken a research programme concerned with the investigation of a bubble type threephase direct contact condenser. Different parameters, which have an effect on the characteristic behaviour of a three-phase direct contact condenser have been investigated experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%